A new look - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
ICT has a new look. Each issue will feature four articles relevant to ICTs for agricultural and rural development in ACP countries, each highlighting a different aspect of the chosen theme, provided by invited experts.